2010
DOI: 10.1119/1.3492723
|View full text |Cite
|
Sign up to set email alerts
|

Less than perfect quantum wavefunctions in momentum-space: How ϕ(p) senses disturbances in the force

Abstract: We develop a systematic approach to determine the large |p| behavior of the momentum-space wavefunction, φ(p), of a one-dimensional quantum system for which the position-space wavefunction, ψ(x), has a discontinuous derivative at any order. We find that if the kth derivative of the potential energy function for the system has a discontinuity, there is a corresponding discontinuity in ψ (k+2) (x) at the same point. This discontinuity leads directly to a power-law tail in the momentum-space wavefunction proporti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 32 publications
(17 reference statements)
4
10
0
Order By: Relevance
“…) , consistent with theorems [25] connecting the discontinuities of ψ(x) (here encoded in the increasingly smooth x S+1 behaviour of the wave functions at the walls) very directly to the large momentum limit of f(p). There are likely many closed-form results waiting to be uncovered in the continued mathematical physics analysis of both the positionspace and momentum-space versions of this problem.…”
Section: Discussionsupporting
confidence: 79%
“…) , consistent with theorems [25] connecting the discontinuities of ψ(x) (here encoded in the increasingly smooth x S+1 behaviour of the wave functions at the walls) very directly to the large momentum limit of f(p). There are likely many closed-form results waiting to be uncovered in the continued mathematical physics analysis of both the positionspace and momentum-space versions of this problem.…”
Section: Discussionsupporting
confidence: 79%
“…where X ij = (m σ x i + m σ ′ x j )/(m σ + m σ ′ ) and x ij = x i − x j are the center of mass and relative coordinates of the two particles. Due to the discontinuity the Fourier transform of the wave-functions at large momenta will have an 1/k 2 asymptotic behavior [67,68]. This fundamental observation will be used extensively throughout this paper and will constitute our main tool in deriving the Tan relations.…”
Section: Model and Correlation Functionsmentioning
confidence: 95%
“…Subsequently, it was shown that they can be rederived using the Operator Product Expansion of local operators [6,7]. Here, we use what we consider to be the most powerful and transparent technique which uses the fact that the derivative of the wave-function of a system with contact interactions is discontinuous when the coordinates of two particles coincide [67,68]. This is the same method employed by Olshanii and Dunjko [5] in their study of the short distance, large momentum distribution of the Lieb-Liniger model and by Werner and Castin in their comprehensive papers on Tan relations for 2D and 3D mixtures [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two of us have developed a systematic description of the large p behavior of φ(p) for one-dimensional problems for which the potential energy function is less than perfect, that is, which has a discontinuous derivative at any order [11]. The general result can be expressed in the following way.…”
Section: φ(P) Beyond the Classical Limitmentioning
confidence: 99%
“…In section 4 we then use these two systems to exemplify new results [11] regarding the large p behavior of the momentum-space wavefunction φ(p) for potentials which are less than perfect, in the sense that they have a discontinuity in some derivative. Two of us have recently shown that if the potential energy function V (x) has a discontinuity in the kth derivative, then the φ(p) solutions exhibit a power-law 'tail', proportional to 1/p k+3 with a coefficient precisely determined by the details of the wavefunction at the location of the generalized 'kink'.…”
Section: Introductionmentioning
confidence: 99%